(3eONd Edi EOGQI GdeYQaIs (3hab YOO ef GdQDi aj GdacQ GdEOGQjs - (3JbGQ(B, (3GeMeOs ((3GdLRGFQs (3OGQ EjdjGA ddfTQ hGdJhRjYs, 2024)
(3EOGQI GdeYQaI aj GdefXhQ GdbGFe Ydi GdehGQO, EOGQI GdeYQaI aj GdefXhQ GdbGFe Ydi GdeYQaI, EOGQI GdeYQaI ef efXhQ GdKbGaI GdJfXjejI, EOGQI GdeYQaI aj GdefXhQ GdJaGYdj Ch GdOjfGejcj, s
Keywords: (3EOGQI GdeYQaIs; (3GdeYQaIs